Uncrossing the borders performing Chinese in gendered (trans)nationalism - Lei, Daphne Pi-Wei (University of Michigan, 2019)
"Over many centuries, women on the Chinese stage committed suicide in beautiful and pathetic ways just before crossing the border for an interracial marriage. Uncrossing the Borders asks why this theatrical trope has remained so powerful and attractive. The book analyzes how national, cultural, and ethnic borders are inevitably gendered and incite violence against women in the name of the nation. The book surveys two millennia of historical, literary, dramatic texts and sociopolitical references to reveal that this type of drama was especially popular when China was under foreign rule, such as in the Yuan (Mongol) and Qing (Manchu) dynasties, and when Chinese male literati felt desperate about their economic and political future, due to the dysfunctional imperial examination system. Daphne P. Lei covers border-crossing Chinese drama in major theatrical genres such as zaju and chuanqi, regional drama such as jingju (Beijing opera) and yueju (Cantonese opera), and modernized operatic and musical forms of such stories today"--
Keywords: Geschichte; Suizid -- Motiv; Mischehe; Drama; Frau; Grenzüberschreitung; Chinesische Oper; Chinese drama / History and criticism; Women in literature; Operas, Chinese / History and criticism; Boundaries in literature; Suicide in literature; Chinese drama; Operas, Chinese; Criticism, interpretation, etc